2021
DOI: 10.1101/2021.05.06.443034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coil-to-Helix Transition at the Nup358-BicD2 Interface Activates BicD2 for Dynein Recruitment

Abstract: Nup358, a nuclear pore protein, facilitates a nuclear positioning pathway that is essential for brain development. Nup358 binds and activates the auto-inhibited dynein adaptor Bicaudal D2 (BicD2), which in turn recruits and activates the dynein machinery to position the nucleus. The molecular details of the Nup358/BicD2 interaction remain poorly understood. Here, we show that a minimal dimerized Nup358 domain activates dynein/dynactin/BicD2 for processive motility on microtubules. Using nuclear magnetic resona… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 119 publications
(318 reference statements)
1
4
0
Order By: Relevance
“…We characterized the BicD2 reactivity with its known cargo protein RanBP2. There are conflicting results in the field with respect to the question whether RanBP2 phosphorylation is a requirement for the interaction with BicD2 (Baffet et al, 2015;Gibson et al, 2021). Our results now reconcile these reports, because they show that BicD2 can bind both non-phosphorylated as well as phosphorylated RanBP2DDB.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We characterized the BicD2 reactivity with its known cargo protein RanBP2. There are conflicting results in the field with respect to the question whether RanBP2 phosphorylation is a requirement for the interaction with BicD2 (Baffet et al, 2015;Gibson et al, 2021). Our results now reconcile these reports, because they show that BicD2 can bind both non-phosphorylated as well as phosphorylated RanBP2DDB.…”
Section: Discussionsupporting
confidence: 82%
“…RanBP2 (or Nup358) is known to recruit BicD2 through a small disordered region between two Ran binding domains as demonstrated in yeast two-hybrid assays (Splinter et al, 2010). The BicD2 binding domain of RanBP2 (hereafter RanBP2BBD) interacts with the C-terminus of BicD2 (715-804) (Gibson et al, 2021) and contains several consensus CDK1 phosphorylation sites, which have been shown to be important for BicD2 binding (Baffet et al, 2015). The individual contribution of these phosphorylation sites to BicD2 binding is unknown.…”
Section: Bicd2's Interaction With Ranbp2mentioning
confidence: 99%
See 1 more Smart Citation
“…RanBP2 (or Nup358) is known to recruit BicD2 through a small disordered region between two Ran binding domains (2003-2444) as demonstrated in yeast two-hybrid assays. 7 The BicD2 binding domain of RanBP2 (hereafter RanBP2BBD) interacts with the C-terminus of BicD2 (715-804) 36 and contains several consensus CDK1 phosphorylation sites, which have been shown to be important for BicD2 binding. 9 However, a recent in-vitro experiment demonstrated that the RanBP2 BBD -BicD2 complex can also be formed in the absence of phosphorylation.…”
Section: Bicd2's Interaction With Ranbp2 and Dynein/dynactinmentioning
confidence: 99%
“…9 However, a recent in-vitro experiment demonstrated that the RanBP2 BBD -BicD2 complex can also be formed in the absence of phosphorylation. 36 Since all these experiments used the truncated BicD2 Cterminus, the binding of the full-length BicD2 to RanBP2 BBD remains to be characterized. In order to clarify the role of phosphorylation in BicD2-RanBP2 BBD complex formation, and to confirm the biochemical activity of our recombinant full-length BicD2, we evaluated the interaction with its binding partner RanBP2.…”
Section: Bicd2's Interaction With Ranbp2 and Dynein/dynactinmentioning
confidence: 99%